A novel mutation in two Hmong families broadens the range of STRA6‐related malformations to include contractures and camptodactyly. Issue 1 (16th September 2015) - Marcadier, Julien L.; Mears, Alan J.; Woods, Elizabeth A.; Fisher, Jamie; Airheart, Cory; Qin, Wen; Beaulieu, Chandree L.; Dyment, David A.; Innes, A. Micheil; Curry, Cynthia J.
Abstract : PDAC (also termed Matthew Wood) syndrome is a rare, autosomal recessive disorder characterized byp ulmonary hypoplasia/aplasia, d iaphragmatic defects, bilaterala nophthalmia, and cardiac malformations. The disorder is caused by mutations in STRA6, an important regulator of vitamin A and retinoic acid metabolism. We describe six cases from four families of Hmong ancestry, seen over a 30 years period in California. These include: (i) consanguineous siblings with a combination of bilateral anophthalmia, diaphragmatic abnormalities, truncus arteriosus, and/or pulmonary agenesis/hypoplasia; (ii) a singleton fetus with bilateral anophthalmia, pulmonary agenesis, cardiac malformation, and renal hypoplasia; (iii) a sibling pair with a combination of antenatal contractures, camptodactyly, fused palpebral fissures, pulmonary agenesis, and/or truncus arteriosus; (iv) a fetus with bilateral anophthalmia, bushy eyebrows, pulmonary agenesis, heart malformation, and abnormal hand positioning. The phenotypic spectrum of PDAC syndrome has until now not included contractures or camptodactyly. Sequencing of STRA6 in unrelated members of families three and four identified a novel, shared homozygous splice site alteration (c.113 + 3_4delAA) that is predicted to be pathogenic. We hypothesize this may represent a unique disease allele in the Hmong. We also provide a focused review of all published PDAC syndrome cases with confirmed or inferred STRA6 mutations, illustrating the phenotypic and molecular variability that characterizes this disorder. © 2015 Wiley Periodicals, Inc.